Antimicrobial efficacy of cryotreatment against Enterococcus faecalis in root canals. (27th December 2012) - Mandras, N.; Allizond, V.; Bianco, A.; Banche, G.; Roana, J.; Piazza, L.; Viale, P.; Cuffini, A.M.
Abstract The purpose of this investigation was to evaluate intracanal bacterial reduction by cryotreatment using a dental instrument equipped with a duct and connected to a cryogenic fluid source. A total of 86 roots were infected with Enterococcus faecalis and incubated. After incubation, the contaminated roots were divided into three study groups: 35 roots irrigated with 2 ml of a 5% sodium hypochlorite (NaOCl) solution, 35 roots irrigated with 2 ml of a 5% NaOCl solution and further treated with cryo and 10 roots irrigated with 2 ml of saline solution, plus positive and negative controls. Subsequent to each irrigation treatment, the residual bacterial colonies were counted. The use of cryo‐instrumentation in association with NaOCl irrigation significantly reduced the number of Ent. faecalis (P < 0·01) in the root canal compared with controls. The interesting potential of cryotreatment should be further investigated through clinical studies aimed to establish a correct irrigation protocol. Within the limits of the study, the cryotreatment seems to have a greater effect on the reduction in bacteria compared to a standard NaOCl irrigation. Significance and Impact of the Study The cryotreatment seems to have a greater effect on the reduction in bacteria compared to a standard NaOCl irrigation. The effect of root canal treatment by the statistically bacterial load reduction on the clinical outcome after cryotreatment remains unknown. The interesting potential of cryotreatment should be further investigated through clinical studies aimed to establish a correct irrigation protocol.